RELOAD/CoAP architecture for the federation of wireless sensor networks - Pisco, Luís (2021)
Sensing devices are expected to interconnect over large geographical areas and federations of wireless sensor networks are expected in a near future. In such environments a critical issue is how to discover the resources available at devices in a scalable manner. For this purpose, a Constrained Application Protocol (CoAP) Usage for REsource LOcation And Discovery (RELOAD), a generic self-organizing Peer-to-Peer (P2P) overlay network service, has been defined to be used as a lookup service, to store available device resources and as a cache for sensor data. Each P2P resource, at the RELOAD/CoAP overlay, includes references to device resources, hosted at one or more constrained nodes, but no provision is made for the insertion of bindings/references to P2P resources already available at the P2P overlay network. Such feature would increase the efficiency and consistency of storage, avoiding duplicate references, a very relevant issue for future IoT applications relying on the federation of wireless sensor networks. In this article an extension to the service provided by CoAP Usage is proposed so that resource bindings can be managed. Two binding models, and a heuristic algorithm for their implementation, are proposed. Results show that such models lead to a better resource organization, reducing the number of sensor resource entries and/or fetches to the P2P overlay.